Segmentasi Konsumen Pupuk Non-Subsidi Di Provinsi Nusa Tenggara Timur - Irwan Hermantria (UMSurabaya Publishing, 2021)
The main goal of the research is to assist market players in entering the fertilizer market in East Nusa Tenggara by identifying and forming a non-subsidized fertilizer consumer segmentation. It is expected to provide market insight for fertilizer producers and determine targets when entering the non-subsidized fertilizer market. This research is a quantitative type described descriptively. The data collection technique was an interview equipped with a questionnaire with a Likert scale of the score. Respondents were food crop and horticultural farmers who use or have used non-subsidized fertilizers. The data analysis technique was the K-Means cluster analysis method. Research succeeded in forming two segments of farmers using non-subsidized fertilizers, passive farmer segment and innovative farmer segment based on psychographics and consumer behavior segmentation variables. Geographic and demographic variable descriptors described the segment profile. Keywords : Fertilizer; Marketing; Non-subsidized; SegmentCorrespondence to : irwan.hermantria-2019@feb.unair.ac.id Tujuan penelitian ini untuk membantu pelaku pasar dalam memasuki pasar pupuk di Nusa Tenggara Timur dengan mengidentifikasi dan membentuk segmentasi konsumen pupuk non-subsidi. Dengan demikian diharapkan mampu memberikan pengetahuan pasar bagi produsen pupuk dalam menentukan target pasar. Penelitian ini merupakan penelitian kuantitatif yang dideskripsikan secara deskriptif. Teknik pengumpulan data dilakukan melalui wawancara yang dilengkapi dengan kuesioner dengan skor menggunakan skala likert. Responden penelitian ini adalah petani tanaman pangan dan hortikultura yang menggunakan atau pernah menggunakan pupuk non-subsidi. Analisis data menggunakan metode Cluster Analysis K-Means. Penelitian ini berhasil membentuk dua segmen petani pemakai pupuk non-subsidi, yaitu segmen petani pasif dan segmen petani inovatif berdasarkan variabel segmentasi psikografis dan perilaku konsumen. Profil segmen dijelaskan oleh deskriptor variabel geografis dan demografis.Kata Kunci : Non-subsidi; Pemasaran; Pupuk; Segmen